(untitled) (The Review of Diabetic Studies, 2025)
Background: Residual cardiovascular risk after acute myocardial infarction (AMI) is driven not only by dyslipidemia but also by systemic inflammation. High-sensitivity C-reactive protein (hs-CRP) and low-density lipoprotein cholesterol (LDL-C) represent two independent and complementary biomarkers of risk. Achieving dual therapeutic targets for both markers has been shown to improve outcomes, yet data in Southeast Asian populations remain scarce. Objectives: This study investigated the prevalence and predictors of failure to achieve hs-CRP and LDL-C targets in post-AMI patients in Vietnam. Methods: A descriptive cross-sectional study was conducted on 93 patients with prior AMI at Tam Duc Heart Hospital between September 2024 and June 2025. Demographic, clinical, and laboratory parameters were collected. hs-CRP and LDL-C levels were measured, and target achievement rates were assessed. Logistic regression analyses were performed to identify independent predictors. Results: Among 93 patients (mean age 66.1 ± 10.1 years, 76.3% male), 24.7% had hs-CRP ≥ 2 mg/L and 43.0% failed to achieve LDL-C < 70 mg/dL. Overall, 51.6% of patients failed to reach at least one target, with 16.1% failing both. Chronic kidney disease, sacubitril/valsartan use, and LDL-C ≥ 70 mg/dL were associated with failure to achieve hs-CRP targets. Diabetes mellitus and elevated hs-CRP were associated with LDL-C non-attainment. Use of ACEI/ARB therapy was identified as a protective factor against dual target failure. Conclusions: A substantial proportion of Vietnamese post-AMI patients fail to achieve dual hs-CRP and LDL-C targets, with diabetes and chronic kidney disease contributing to residual risk. These findings underscore the need for intensified secondary prevention strategies addressing both lipid and inflammatory pathways.